(untitled) (Ecological Bulletin of Kryvyi Rih District, 2023)
The issue of optimizing the urban environment is of primary importance in the modern conditions of the rapid process of urbanization. Plants that are sensitive to environmental pollution and have a quick reaction to the presence of even small doses of toxic substances in the air play an important role in the system of measures to improve the ecological state of cities; therefore, they are considered the best indicators of the state of the air environment. Usually, the assessment of the state of ecological systems is carried out according to various ecological standards and regulations. Among them, the most important are environmental quality standards, which are expressed in indicators of maximum permissible concentrations of harmful substances in individual environmental objects. Such approaches are based only on instrumental physico-chemical methods of analysis and are focused on monitoring compliance with standardized indicators. However, such methods do not always timely illustrate the full picture of the impact of pollutants on biota in technogenical-loaded regions, where there is a constant risk of increasing the genetic stress of the environment, which is caused to entry into the ecotopes of pollutants with pronounced mutagenic activity. Therefore, recently a well-founded trend of assessment of the transformed ecosystems state traced not only by traditional physicochemical methods, but also by bioindication methods. Bioindicative methods make it possible to determine the complex effect of all pollutants present in environmental objects; they are highly sensitive and sufficient for adequate assessments. Long-term studies on the assessment of the Kryvyi Rih city ecological condition have reasonable results and its based, as a rule, on the use of standard methods. Bioindication, as an alternative and promising approach in such studies, is not widespread enough and using very rarely. The article summarizes information about the use of plants in bioindicative studies of the Kryvyi Rih city. The use of woody and herbaceous plants in ecological stress determining of the city is compared. The significance of bioindication for monitoring studies of the city territory is considered. The perspective of using cytogenetic bioindicative studies for the integrated assessment of the environment of the Kryvyi Rih iron ore region is analyzed.